PSIX-35 Finishing feeding strategies for dairy steers based on summer turnip and their effects on beef quality produced in south Chile. (7th December 2018) - Morales, R; Subiabre, I; Lara, J; Larraín, R; Sales, F
Abstract: Because of its fast growth, high forage yield and nutritive value summer turnips (Brassica rapa L.) have become one of the main supplementary crops in livestock systems of southern Chile. There is information of its effect on the productive response of beef cattle, although its effect on beef characteristics has not been studied. The objective of this study was to evaluate the summer supplementation of turnips on the beef characteristic of dairy steers. Holstein Friesian steers ( n =27; 406kg live weight) were allocated to 3 treatment groups (n=9): pasture plus concentrate (Control), 50% turnips (T50 ), and 70% turnips (T70 ). The two last diets with hay and maize. The performance productive of the steers were determined. The physicochemical and sensory attributes, and the fatty acid composition of the longissimus dorsi muscle were determined. The pasture-fed steers showed higher weight gain than turnips-fed animals. T50 beef showed higher intramuscular fat and pasture-fed steers showed higher fat thickness. Turnips finishing increased the proximal composition (MS%; PC%; EE% and Ash% (Fe%, Na%, Mn%)), PUFA ( polyunsaturated fatty acids ) and redder, whereas shear force and lightness fat tended to decrease. Pasture-fed had the higher 11 t -/10t-18:1 ratio and less cholesterol content than turnips-fed steers. Pasture and turnips reduced the n -6/ n -3 ratio (<4) in muscle tissue. Forage turnip is an attractive option to ensure nutritional quality of the meat during periods of low pasture growth.